Scopolamine 유발 기억 손상 마우스 모델에서 국산 산사와 중국산 산사의 항건망 효과 비교 - 이지혜(Jihye Lee); 김혜정(Hye-Jeong Kim); 이찬희(Chanhee Lee); 박상혁(Sang Hyeok Park); 정철종(Chul Jong Jung); 백경연(Gyung Yun Beik); 신진기(Jin Gi Shin); 정지욱(Ji Wook Jung) (동의생리병리학회지, 2018)
This study was conducted to investigate the cognitive improvement and memory recovery effects of Korean and Chinese Crataegus pinnatifida ethanolic extracts on scopolamine-induced memory impairment in mice. In vivo studies were carried out with mice treated with Korean Crataegus pinnatifida extracts (KCF) and Chinese Crataegus pinnatifida extracts (CCF) in doses of 5 and 50 mg/kg (p.o.) and scopolamine was injected 30 min before the behavioral testing. Antioxidant activity was assessed by 2,2-diphenyl-1-picryl hydrazyl (DPPH) assay and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay, and acetylcholinesterase inhibition by Ellman's modified method. The chlorogenic acid and hyperoside as marker compounds of KCF and CCF was quantified by ultra-performance liquid chromatography analysis (UPLC). Results showed that KCF was more contained high content of chlorogenic acid and hyperoside than CCF. In addition, KCF was more exerted free radical (DPPH and ABTS) scavenging activity and blocked AChE activity than CCF. In vivo studies also showed that KCF administration has a further improved the memory of scopolamine-treated mice than CCF in Y-maze test, passive avoidance test and Morris water maze test. These results revealed that KCF more prevents scopolamine-induced memory impairments through antioxidant and acethylcholinesterase inhibition effect compared CCF.